The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2991/assehr.k.211209.429
|View full text |Cite
|
Sign up to set email alerts
|

Brand New Milk Tea Market: Chinese Milk Tea Development and Brand Analysis

Abstract: Since the beginning of the 20th century, the milk tea industry grew rapidly in China and has become a popular leisure activity for young people. According to the study of three chain stores in China, low-end milk tea stores are inexpensive and affordable, while mid-range milk tea stores have a wide variety and high-end milk tea stores focus on visual effects. The core competitiveness of enterprises could be the ability to continuously push new products and supply chains. Some top brands with perfect supply cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…In 2021, Dedi did research to find the relationships between consumers' purchasing decisions and the features of products, such as product form, product quality, product type, product utilization, and product durability, and he found that the effect of the Product Features variable on the purchasing decision variable is positive and significant [4]. Further in the investigation of milk tea that Wingnam and others did in 2021, they found that product research and innovation would establish technical competitiveness and give the company a new growth point to meet the diversified consumer needs and establish consumer loyalty [5]. Therefore, companies should enrich product content and features and make innovations to attract more consumers and increase consumers' purchasing intention.…”
Section: Important Resultsmentioning
confidence: 97%
“…In 2021, Dedi did research to find the relationships between consumers' purchasing decisions and the features of products, such as product form, product quality, product type, product utilization, and product durability, and he found that the effect of the Product Features variable on the purchasing decision variable is positive and significant [4]. Further in the investigation of milk tea that Wingnam and others did in 2021, they found that product research and innovation would establish technical competitiveness and give the company a new growth point to meet the diversified consumer needs and establish consumer loyalty [5]. Therefore, companies should enrich product content and features and make innovations to attract more consumers and increase consumers' purchasing intention.…”
Section: Important Resultsmentioning
confidence: 97%
“…To inspect Mixue's financial gain, this study shows the brand's sales growth and market share size [7] over the years. In addition, the quantitative growth of the overall Chinese milk tea industry is also taken into consideration, such as the accumulative Chinese milk tea market size, the market share percentage of different milk tea brand tiers [8], and the regional distributions of milk tea stores in China [9]. The evaluation of Mixue's social media presence and influence will be done by looking at Mixue's follower numbers on different social media platforms, and the view counts of Mixue's uploaded contents.…”
Section: Discussionmentioning
confidence: 99%
“…The attributes examined in this study were obtained from real market research and previous studies. When conducting market research on milk tea, our research team recorded and analyzed the menus of famous milk tea shops in the Fujian Province, such as CoCo, Gongcha, Alittle, Nayuki, and Heytea, which are the most popular brands across China [ 22 , 32 , 45 ]. As milk tea consist of a tea base and other ingredients [ 46 , 47 ], attributes were chosen based on those two categories and comprised the type of the tea base, the origin of tea leaves, added ingredients, and the milk brand.…”
Section: Experimental Procedures and Datamentioning
confidence: 99%
“…As for the various brands of milk tea products, the future milk tea market is predicted to bloom and continue to be competitive, and as such, there are various directions in which brands can develop, such as implementing personalized branding [ 45 ]. Taking the marketing strategies of realistic milk tea market into consideration, current brand subsidiaries of famous tea brands and new brands are chosen as the different levels of attribute.…”
Section: Experimental Procedures and Datamentioning
confidence: 99%